2005
DOI: 10.1002/jts.20021
|View full text |Cite
|
Sign up to set email alerts
|

Motives to drink as mediators between childhood sexual assault and alcohol problems in adult women

Abstract: Two models are proposed to relate maladaptive emotion regulation strategies and alcohol-related problems for women with a history of childhood sexual assault (CSA). The distress coping model suggests only one motive-drinking to cope with negative emotions-mediates the relationship between CSA and alcohol problems. The emotion regulation model suggests two motives mediate the relationship between CSA and alcohol problems: drinking to cope with negative emotions and drinking to enhance positive emotions. These m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
139
6
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 38 publications
(49 reference statements)
16
139
6
2
Order By: Relevance
“…In addition, they are more likely to engage in risky sexual behavior, have an eating disorder, or attempt suicide (Castillo Mezzich et al, 1997;Kendler et al, 2000;Polusny & Follette, 1995;Rodriguez-Srednicki, 2002). Problematic substance use and early onset of drinking are also associated with early childhood trauma (Douglas et al, 2010;Dube et al, 2006;Epstein et al, 1998;Grayson & Nolen-Hoeksema, 2005;Lo and Cheng, 2007;Polusny & Follette, 1995;Shin et al, 2009;Simpson & Miller, 2002). In one study of 1,411 female adult twins, those who reported childhood sexual assault (30.4%) were at a threefold increased risk of becoming dependent on alcohol or other drugs (Kendler et al, 2000).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they are more likely to engage in risky sexual behavior, have an eating disorder, or attempt suicide (Castillo Mezzich et al, 1997;Kendler et al, 2000;Polusny & Follette, 1995;Rodriguez-Srednicki, 2002). Problematic substance use and early onset of drinking are also associated with early childhood trauma (Douglas et al, 2010;Dube et al, 2006;Epstein et al, 1998;Grayson & Nolen-Hoeksema, 2005;Lo and Cheng, 2007;Polusny & Follette, 1995;Shin et al, 2009;Simpson & Miller, 2002). In one study of 1,411 female adult twins, those who reported childhood sexual assault (30.4%) were at a threefold increased risk of becoming dependent on alcohol or other drugs (Kendler et al, 2000).…”
mentioning
confidence: 99%
“…This work was initiated to find support for the self-medication theory that posits that individuals with a trauma history will use substances to decrease negative affect (Khantzian, 1985). Although using substances may be an effective, yet damaging, method for coping with the distressing symptoms of trauma, the authors of recent studies have argued that alcohol may also be a means to increase positive emotion (Goldstein et al, 2010;Grayson and Nolen-Hoeksema, 2005;Nugent et al, 2012;Simpson, 2003;Simpson et al, 2014). For example, Simpson and colleagues (2014) found that both coping motives for dealing with negative affect and enhancement motives to increase positive affect moderated the relationship between sameday alcohol use and PTSD symptoms as well as increased drinking in those men and women with comorbid PTSD and alcohol dependence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol use often serves as a maladaptive coping strategy for victims of CM (Filipas and Ullman, 2006), and its use may differ based on its motivations (Grayson and Nolen-Hoeksema, 2005). For example, victims of CM may drink to enhance positive emotions or drink to cope with negative emotions.…”
mentioning
confidence: 99%
“…Studies of PTSD and addiction consistently imply that women with dual diagnosis are often survivors of severe interpersonal childhood trauma (Back et al, 2003;Grayson & Nolen-Hoeksema, 2005;Grella et al, 2005;Marcenko et al, 2000;Najavits et al, 1999). These women are also likely to present with a more severe clinical profile on all socio-demographic variables and with more distorted thinking than women with a single diagnosis of either disorder (Back et al, 2003;Najavits, Gotthardt, Weiss, & Epstein, 2004).…”
Section: Assessmentmentioning
confidence: 99%